The Reality of Practicing Governance Principles and its Relation to Enhance the Administration Quality of Educational Institutions in Algeria - Imane , Zitouni; Djahid , Boutaleb (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to identify the reality of practicing governance principles (transparency, equity and Fairness, accountability, participation) and their relationship with the quality of administration of educational institutions in Algeria. Methods: The study adopted the descriptive correlational approach, where a questionnaire was designed as a tool for data collection, it consisted of two axes: the first pertains to the reality of practicing governance principles and included (27) items, the second concerns the quality of administration of educational institutions and included (5) items, these were distributed to a sample of (215) directors of educational institutions. Results: The study’s outcomes reveal a substantial level of adherence to governance principles within Algerian educational institutions, from the perspective of the study sample members, The principle of fairness leads in application, followed by transparency, accountability, and participation. Moreover, a statistically significant relationship was identified between the degree of practicing of governance principles (transparency, equity and Fairness, accountability, participation) and the quality of administration of educational institutions in Algeria. Conclusions: The study recommended the enhancement of oversight and accountability mechanisms in educational institution management through the formation of specialized committees and the continuous reinforcement of educational management laws and regulations in alignment with governance principles.